“Everything Now Falls on Me”: Parent Perspectives on Services Lost and Challenges During Virtual Learning for Youth with Disabilities - Munsell, Elizabeth G. S.; Schwartz, Ariel E.; Schmidt, Elizabeth K.; Chen, Jennifer (Journal of the American Academy of Special Education Professionals, 2021)
The COVID-19 outbreak caused abrupt disruptions to many domains of everyday life, including education. Educational disruptions may be compounded for students who require supports and services to participate. We surveyed parents of students with disabilities and chronic health conditions to understand the extent of service delivery disruption, challenges experienced with virtual learning, and the impact of these changes on their and their students’ lives. Thirty-seven parents completed an online survey consisting of multiple-choice and open-ended questions from May-August 2020. Data were analyzed using a convergent mixed-methods approach using descriptive and content analyses of survey data. Parents reported their students’ educational needs are not met in the virtual environment and parents are taking on new roles to support their students’ learning. The need to provide intensive supports resulted in parental frustration and burnout. We offer potential approaches to improve educational service delivery for students with disabilities during the COVID-19 pandemic.